Call It a Femicide: Missing and Murdered Indigenous Women and Girls - Villalobos, Johanna (The Toro Historical Review, 2025)
This essay explores the troubling reality in North America, where a disproportionately high number of Indigenous women and young girls are going missing or being murdered (MMIWG), yet these tragedies often fail to receive adequate media attention or law enforcement resources compared to cases involving white women. Systemic issues like racism, sexism, socio-economic inequalities, and damaging stereotypes contribute to the marginalization of these cases. This disparity underscores deep-seated prejudices and failures within institutions, rooted in historical injustices. Research into the crisis of missing and murdered Indigenous women and girls (MMIWG) reveals the persistent legacy of colonialism, as explored in Sarah Deer's book, The Beginning and End of Rape. Colonization allowed European men to assert power over Indigenous women, fostering a legacy of control and subjugation that has led to ongoing systemic challenges, such as heightened sexual violence and human trafficking in Indigenous communities today. This essay examines the impact of sexual violence through primary and secondary sources, the lack of action by the government and police in investigating MMIWG, the role of the media in shaping the crisis, and the activism and movements within Indigenous communities aimed at decolonizing the narrative to advocate for justice and remembrance. The essay concludes by emphasizing the growing awareness and activism among Indigenous peoples and their allies to confront these critical issues. This effort not only honors the victims and their families but also challenges the persistence of such violence. Ultimately, the research aims to contribute to a deeper understanding of the structural inequalities driving this epidemic in North America.